Characterization of Magnitude and Antigen Specificity of HLA-DP, DQ, and DRB3/4/5 Restricted DENV-Specific CD4+ T Cell Responses - Grifoni, Alba; Moore, Eugene; Voic, Hannah; Sidney, John; Phillips, Elizabeth; Jadi, Ramesh; Mallal, Simon; De Silva, Aruna D.; De Silva, Aravinda M.; Peters, Bjoern; Weiskopf, Daniela; Sette, Alessandro (Frontiers in Immunology, 2019)
Background: Dengue Virus (DENV) associated disease is a major public health problem. Assessment of HLA class II restricted DENV-specific responses is relevant for immunopathology and definition of correlates of protection. While previous studies characterized responses restricted by the HLA-DRB1 locus, the responses associated with other class II loci have not been characterized to date. Accordingly, we mapped HLA-DP, DQ and DRB3/4/5 restricted DENV-specific CD4 T cell epitopes in PBMCs derived from the DENV endemic region Sri Lanka. Methods: We studied twelve DP, DQ and DRB3/4/5 alleles that are commonly expressed and provide worldwide coverage greater than 82% for each of the loci analyzed and greater than 99% when combined. CD4+ T cells purified by negative selection were stimulated with pools of HLA-predicted binders for two weeks with autologous APC. Epitope reactive T cells were enumerated using IFNγ ELISPOT assay. This strategy was previously applied to identify DRB1 restricted epitopes. In parallel, membrane expression levels of HLA-DR, DP and DQ proteins was assessed using flow cytometry. Results: Epitopes were identified for all DP, DQ and DRB3/4/5 allelic variants albeit with magnitudes significantly lower than the ones previously observed for the DRB1 locus. This was in line with lower membrane expression of HLA- DP and DQ molecules on the PBMCs tested, as compared to HLA-DR. Significant differences between loci were observed in antigen immunodominance. Capsid responses were dominant for DRB1/3/4/5 and DP alleles but negligible for the DQ alleles. NS3 responses were dominant in the case of DRB1/3/4/5 and DQ but absent in the case of DP. NS1 responses were prominent in the case of the DP alleles, but negligible in the case of DR and DQ. In terms of epitope specificity, repertoire was largely overlapping between DRB1 and DRB3/4/5, while DP and DQ loci recognized largely distinct epitope sets. Conclusion: The HLA-DP, DQ and DRB3/4/5 loci mediate DENV-CD4 specific immune responses of lower magnitude as compared to HLA-DRB1, consistent with their lower levels of expression. The responses are associated with distinct and characteristic patterns of immunodominance, and variable epitope overlap across loci.